Awareness of anterior cruciate ligament injury-preventive training programs among female collegiate athletes - Tanaka, M. J.; Jones, L. C.; Forman, J. M. (Journal of Athletic Training, 2020)
Context: Neuromuscular training programs can reduce the rate of noncontact anterior cruciate ligament (ACL) injuries, particularly in female athletes. Objective: To assess the awareness of, experience with, and factors associated with participation in preventive training programs (PTPs) among female collegiate athletes and their knowledge of ACL injuries. Design: Cross-sectional study. Setting: National Collegiate Athletic Association (NCAA) sports programs. Patients or Other Participants: A total of 440 female NCAA athletes (age = 20 ± 1 years) representing 20 sports during the 2017-2018 academic year. Main Outcome Measure(s): We used a 12-item survey to collect data on each participant's age, sport, position, college, NCAA division, and awareness of and experience with PTPs. We performed descriptive statistics and used odds ratios (ORs) to assess relationships between demographic data and awareness of or interest in PTPs. Results: Of the 440 respondents, 85% (n = 373) knew that female athletes were at higher risk for sustaining ACL injuries than male athletes, and 89% (n = 391) knew that ACL injuries were preventable. Thirty-three percent (n = 143) were familiar with the concept of ACL PTPs. Only 15% (n = 64) had ever performed PTPs, but 89% (n = 391) reported they would perform a daily PTP if it could prevent ACL injuries. Fifty-two of the 64 respondents (81%) who had performed PTPs said athletic trainers or coaches oversaw the PTPs. Participants were more likely to be familiar with ACL PTPs if they (OR = 3.5; 95% confidence interval [CI] = 2.0, 5.8) or a teammate (OR = 4.6; 95% CI = 2.1, 9.8) had sustained an ACL injury. Respondents were more willing to perform PTPs if they (OR = 2.3; 95% CI = 0.80, 6.6) or a teammate (OR = 3.4; 95% CI = 1.8, 6.6) had sustained an ACL injury. Conclusions: Although 89% of respondents expressed interest in performing daily ACL PTPs, only 15% had performed such programs, and only 33% were familiar with the concept of ACL PTPs.